2018
DOI: 10.3389/fpsyg.2018.01355
|View full text |Cite
|
Sign up to set email alerts
|

Use and Usefulness of Dynamic Face Stimuli for Face Perception Studies—a Review of Behavioral Findings and Methodology

Abstract: Faces that move contain rich information about facial form, such as facial features and their configuration, alongside the motion of those features. During social interactions, humans constantly decode and integrate these cues. To fully understand human face perception, it is important to investigate what information dynamic faces convey and how the human visual system extracts and processes information from this visual input. However, partly due to the difficulty of designing well-controlled dynamic face stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 79 publications
2
80
1
Order By: Relevance
“…For example, identifying facial motion not only enhances the understanding of facial expression, but can also improve the perception of other face aspects like speech comprehension (as best evidenced in the hearing impaired), in addition to the perception of gender and identity. 2 This process of integrating the additional cues from facial movement with facial form is termed static-dynamic integration. Also, the traditional belief that the cortical cascade of visual processing is a bottom-up process initiating in the occipital cortex, and then projecting to prefrontal cortex for higherlevel processing only after the object is identified completely in the fusiform gyrus, is changing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, identifying facial motion not only enhances the understanding of facial expression, but can also improve the perception of other face aspects like speech comprehension (as best evidenced in the hearing impaired), in addition to the perception of gender and identity. 2 This process of integrating the additional cues from facial movement with facial form is termed static-dynamic integration. Also, the traditional belief that the cortical cascade of visual processing is a bottom-up process initiating in the occipital cortex, and then projecting to prefrontal cortex for higherlevel processing only after the object is identified completely in the fusiform gyrus, is changing.…”
Section: Discussionmentioning
confidence: 99%
“…However, this format has been argued to be less ecologically valid (Krumhuber et 16 al., 2013;Recio et al, 2011). While this assumption is still subject to some controversy (see 17 Dobs et al, 2018, for details), future studies would benefit from using datasets of more 18 naturalistic stimuli to further increase ecological validity. 19…”
Section: Testosterone Cortisolmentioning
confidence: 99%
“…Another issue in the field of emotional faces concerns the properties of the stimuli that are used. As summarized in a recent review (Dobs et al, 2018), different types of facial stimuli can be considered (e.g., static vs dynamic; real vs synthetic). Although most research has looked at static faces, a number of studies have suggested that dynamic facial expressions benefit recognition in certain conditions (for a review, see Krumhuber et al, 2013), even if interpretations (e.g., attention driven, facilitation of mimicry behavior) are still sparse (e.g., Calvo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although most research has looked at static faces, a number of studies have suggested that dynamic facial expressions benefit recognition in certain conditions (for a review, see Krumhuber et al, 2013), even if interpretations (e.g., attention driven, facilitation of mimicry behavior) are still sparse (e.g., Calvo et al, 2016). Given their respective advantages and disadvantages (Dobs et al, 2018), stimuli need to be chosen according to the research objective. In this vein, studies featuring PLDs are growing in popularity.…”
Section: Introductionmentioning
confidence: 99%